Hyaline globules and papillary fragments in cytologic smears from two intra‐abdominal tumors (ovarian and hepatic) in female patients: A diagnostic pitfall with histologic correlation. Issue 11 (13th July 2016) - Machado, Isidro; López‐Soto, María Victoria; Pérez‐López, Albadio Samir; Domínguez‐Álvarez, Carlos; Llombart‐Bosch, Antonio
Abstract : Hyaline globules and papillary fragments in cytologic samples from two intra‐abdominal tumors in young females are presented including the cytological features and the correlation with the histopathologic and immunohistochemical findings. In the first case a cytologic study from an ovarian mass showed papillary structures and isolated tumor cells with epithelioid morphology, irregular reniform‐like nuclear contour, pale or vacuolated cytoplasm, abundant hyaline globules and occasional glomeruloid structures resembling Schiller‐Duval bodies. Yolk sac tumor (YST) was the diagnosis on the histological slides. Tumor cells showed positivity for cytokeratin (AE1/AE3), epithelial membrane antigen (EMA), alpha‐fetoprotein (AFP) and Sal‐like protein 4 (SALL4). In case number two the cytologic study from a liver metastasis displayed papillary and rosette‐like clusters composed of uniform and bland cells showing occasional long cytoplasmic tails, hyaline globules and nuclear grooves. A diagnosis of hepatic metastasis from solid pseudopapillary neoplasm of the pancreas (SPNP) was rendered from the histology. Tumor cells revealed immunoreactivity for cytokeratin (AE1/AE3), Vimentin, Galectin‐1 (GAL‐1), Neuron specific‐enolase, CD10, progesterone and β‐catenin (nuclear stain). Regarding differential diagnosis, in the patient with the ovarian mass an ovarian clear cell carcinoma was considered, as well as other germ cell tumors or metastatic carcinoma, while in the patient with a liver metastasis a neuroendocrine carcinoma was taken into account. YST and SPNP share some cytological findings, including hyaline globules, papillary structures, clear cells and intercellular eosinophilic basement membrane deposits. Thus, a detailed study and careful interpretation of the cytological, histological and immunohistochemical findings may be worthwhile to avoid a potential misdiagnosis, particularly in the cytologic specimens of the ovarian and/or intra‐abdominal mass, when involving young females. Diagn. Cytopathol. 2016;44:935–943. © 2016 Wiley Periodicals, Inc.